Optimalisasi Pemanfaatan Limbah Bonggol Jamur Tiram Dalam Upaya Peningkatan Varian Produk Unggulan Pada AJJ Jamur Jepara - Kusumodestoni, R Hadapiningradja; Sagaf, M; Setiyowati, Desti; Hidayat, Solikhul (Amalee: Indonesian Journal of Community Research and Engagement, 2023)
Utilization of oyster mushroom weevil waste is an effort to add superior product variants, processed mushrooms are intended as an effort to increase sales turnover at AJJ Mushrooms Jepara. For the waste to be useful again, it is necessary to optimize it through the utilization of oyster mushroom waste into processed mushroom sticks. This assistance needs to be carried out to reuse oyster mushroom hump waste which was previously only used for additional animal feed and increase the selling value of processed waste. The method used in this community service is the Assed Based Community Development ABCD method through the activities of providing assistance and training through outreach, practice, and demonstrations to partners starting from the preparation of materials in the form of mushroom cob waste, other supporting materials, equipment, resource persons whom are some expert in processing food ingredients followed by outreach activities, practice, and direct assistance to partners. The result of mentoring the utilization of oyster mushroom weevil waste is in the form of mushroom sticks that are crispy and delicious to events that they can increase product variants selling processed mushrooms and increase the number of sales turnover at AJJ Jepara Oyster Mushrooms.